Buddhist Painting in the South of the Tarim Basin: A Chronological Conundrum - Muzio, Ciro Lo (Dynamics in the history of religions, 2022)
These notes deal with Buddhist paintings from the south of the Tarim Basin, more specifically with those unearthed in the Khotan oasis and, farther east, at Karadong, in the basin of the Keriya River. The findings were yielded by excavations carried out in the early decades of the 20th century and again, after a long gap, from the 1990s until recently. The methods of the field investigations that led to their discovery and the accuracy of their documentation are dramatically diverse, as are the criteria upon which the chronology of the murals has been formulated: from the 3rd century (Karadong) to the 6th-8th centuries (Khotan oasis). Such a long chronological span seems to be at odds with the relative proximity the murals display in their iconographic and stylistic orientation. This paper presents a state of art of the topic and a preliminary attempt to spot clues that may lead to a more balanced chronological perspective.